2018
DOI: 10.1186/s13058-018-1008-9
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate carboxylase supports the pulmonary tropism of metastatic breast cancer

Abstract: BackgroundOvercoming systemic dormancy and initiating secondary tumor grow under unique microenvironmental conditions is a major rate-limiting step in metastatic progression. Disseminated tumor cells encounter major changes in nutrient supplies and oxidative stresses compared to the primary tumor and must demonstrate significant metabolic plasticity to adapt to specific metastatic sites. Recent studies suggest that differential utilization of pyruvate sits as a critical node in determining the organotropism of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 32 publications
0
66
0
Order By: Relevance
“…One of these adaptations has been observed during breast‐derived lung metastasis where, once early metastatic lesions are established, pyruvate further drives PC activity, which supports the TCA cycle anaplerosis needed for proliferation (Christen et al , ). Accordingly, genetic deletion of PC impaired pulmonary but not extra‐pulmonary metastasis—suggesting that PC activity could be important for organ tropism (Shinde et al , ). The metabolic changes induced by the organ microenvironment were also found to be reversible with the observation that transplanting liver metastasis‐derived cancer cells back into the primary subcutaneous site induced a parental metabolic state (Piskounova et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these adaptations has been observed during breast‐derived lung metastasis where, once early metastatic lesions are established, pyruvate further drives PC activity, which supports the TCA cycle anaplerosis needed for proliferation (Christen et al , ). Accordingly, genetic deletion of PC impaired pulmonary but not extra‐pulmonary metastasis—suggesting that PC activity could be important for organ tropism (Shinde et al , ). The metabolic changes induced by the organ microenvironment were also found to be reversible with the observation that transplanting liver metastasis‐derived cancer cells back into the primary subcutaneous site induced a parental metabolic state (Piskounova et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Another important regulator of the tumorigenic process is the tumor secretome. The secretome consists of key regulatory molecules, derived from the primary tumor or tumor‐associated cells, which influence the microenvironment of secondary organs—priming them for the cultivation of secondary tumors (Shinde et al , ). In this regard, recent metabolomics analysis of the in vivo secretome of lung cancer models revealed that increased succinate secretion into plasma by cancer cells induces macrophage‐dependent cytokine signaling in the metastatic niche (Wu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a rate-limiting enzyme that catalyzes the decarboxylation of pyruvate to form acetyl-CoA. In recent years, the role of PC in tumor cells has been gradually reported (31). Stefan Christen et al (32) found that the process of lung metastasis in breast cancer relies on the glucose metabolism pathway that PC participates in.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is a complex, heterogeneous disease, and it is also the most cause of cancer death among women around the world (105,132,167). Glycolysis is the main energy source for most solid tumors under hypoxic environment (130,164).…”
Section: Role Of Hno Donors or Its Derivatives In Different Cancersmentioning
confidence: 99%